Journal of Asian Earth Sciences - Journal of Asian Earth Sciences (Elsevier, 2026)
The Journal of Asian Earth Sciences is an international interdisciplinary journal devoted to all aspects of research related to the solid Earth Sciences of Asia. The Journal publishes high quality, peer-reviewed scientific papers on the regional geology, tectonics, geochemistry and geophysics of Asia. It will be devoted primarily to research papers but short communications relating to new developments of broad interest, reviews and book reviews will also be included. Papers must have international appeal and should present work of more than local significance.
FI 0.76
Q2
Keywords: Earth; Space & Environmental Sciences; Environmental Geoscience; Geociencia; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Procesos profundos y superficiales; recursos y cambio climático en Asia